Acute Toxicity Testing of White Turmeric Extract (Curcuma zedoaria) on Histopathological Imaging of the Lungs - Ainge Rasbina Br Saragih; Fiska Maya Wardhani; Erny Tandanu; Rico Alexander (HM Publisher, 2021)
White turmeric (Curcuma zedoaria) is a type of plant whose extract contains compounds that can inhibit carcinogenesis. Acute toxicity test was conducted to determine the safe dose and lethal dose (LD) 50 from the use of a drug substance. This research aimed to determine the effect of the acute toxicity test of white turmeric extract on the histopathological imaging of the lungs. This study is an experimental study with a post test only control group design. A total of 30 Wistar rats was divided into six groups. Data analysis was using one-way ANOVA statistical test, while for lung histopathology using ordinal data which were analyzed descriptively. In conclusion, the acute toxicity test of white turmeric extract on Wistar rats was not toxic and there was no death and no toxic symptoms and no necrosis, congestion and inflammation were found on the histopathological picture of the lungs.